Exploring Financial Health in India: Evaluating Risks for Sustainable Practices - Dr. Sunil Kumar (Innovative Research Thoughts, 2023)
Stakeholder theory is the foundation for environmental, social, and governance (ESG) factors, which are crucial for sustainable corporate operations. This study looks at the effects that various ESG risk levels have on Indian financial companies' financial performance. The Prowess IQ database provided the data for this investigation. The study found, in keeping with stakeholder theory, a substantial negative association between ESG risk and a company's return on equity and return on assets through the use of correlation analysis and linear regression. These results emphasise how crucial it is for businesses to concentrate on lowering ESG risks in order to increase profitability. This study fills a knowledge gap about the relationship between ESG characteristics and financial performance, particularly in the context of the Indian financial sector, due to the paucity of research in this field.